A Study of Visual Background of Animal Crossing: New Horizons Game - Abasi, Yuyun Wahyuni; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
As a visual medium, Animal Crossing: New Horizons is a social simulation game with a beautiful visual design set in nature, which became one of the most popular games during the Covid-19 pandemic when people were required to stay at home. The advantage of this game made by Nintendo for the Nintendo Switch console from similar games is its real-time system. The time situation in real life occurs the same as in the game, so the visual background changes according to real-time. Previous research has discussed the gameplay and the relationship between this game’s popularity during the pandemic, and this research is about its visual background. This study is intended to determine the background visualization displayed in the Animal Crossing: New Horizons game based on the time of day changes in four different seasons. The method used in this study is a descriptive method to expose the types of visual backgrounds for four seasons in the Animal Crossing: New Horizons game. Data collection was carried out through literature studies and observations. Based on the time shift in each season in the morning, noon, afternoon, and evening in four seasons, the findings generated up to 16 visual backgrounds.